2017
DOI: 10.1111/1755-6724.13069
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Conditions of Evaporites in the Late Jurassic Xiali Formation, Qiangtang Basin: Evidence from Geochemistry Records

Abstract: The Qiangtang Basin (QB), located in the central Tibetan Plateau, is a Jurassic marine basin and one of the most important prospective salt resource belts in China. In recent decades, many outcrops of gypsiferous bed have been found in the Jurassic marine strata in the basin. Salt springs with abnormally high sodium (Na+) contents had been identified in the Late Jurassic Xiali Formation (Fm.) in the basin in the last years. However, to date, no potash or halite deposits have been identified in the QB. Gypsum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…of the South Qiangtang; Wang, Tan, Li et al, ). The upper sequences of the Middle Jurassic consist of marine platform limestones, dolomites (Buqu Fm., Ding, Wan, Zhang, & Han, ) and regressional semi‐closed tidal flat sediments (Xiali Fm., Song, Zeng et al, ). The Upper Jurassic unit is represented by intra‐platform littoral‐neritic carbonate rocks and black shales deposited in a closed, deep and static marine environment (Suowa Fm., Wang, Zhang, Cai, & Han, ).…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…of the South Qiangtang; Wang, Tan, Li et al, ). The upper sequences of the Middle Jurassic consist of marine platform limestones, dolomites (Buqu Fm., Ding, Wan, Zhang, & Han, ) and regressional semi‐closed tidal flat sediments (Xiali Fm., Song, Zeng et al, ). The Upper Jurassic unit is represented by intra‐platform littoral‐neritic carbonate rocks and black shales deposited in a closed, deep and static marine environment (Suowa Fm., Wang, Zhang, Cai, & Han, ).…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…Ion contents are also important indicators of the sedimentary environment [48]. The high content of Na + and low ranges of Ca 2+ and Mg 2+ of the water in the central and western parts of the study area show that the underground coalbed was in a closed groundwater environment.…”
Section: -mentioning
confidence: 96%
“…The methods of sandbody isopach mapping, sandbody top contour mapping, geochemistry records and well logging microfacies analysis amalgamation were adopted (Song et al, 2017), and we found that the abandoned channel of the meandering river is laterally associated with the point bar, which is the convex bank boundary at the Fig. 6.…”
Section: Influence Of Abandoned Channels On Oilfield Water Floodingmentioning
confidence: 98%